Iodine Monoacetate for Efficient Oxyiodinations of Alkenes and Alkynes - Hokamp, Tobias; Storm, Alena Therese; Yusubov, Mekhman; Wirth, Thomas (Synlett, 2018)
A novel and inexpensive, environmentally friendly method for the preparation of iodine monoacetate is presented using iodine and Oxone in acetic acid/acetic anhydride. The reagent is used in a highly efficient approach for the regio- and diastereoselective iodoacetoxylation of alkenes and alkynes in a simple one-pot process.
Keywords: alkenes; alkynes; iodine; iodine(I)acetate; oxyiodination